Exploring Psychosocial Variables and Professional Well‐Being in Nurse Leaders: A Predictive Correlational Study. - Urban, Regina W.; Martin, Shirley D.; Bailey, Stephanie; Rivera, Norma; Lim, Maria Lourdes C.; Bracco, Shonna (Worldviews on Evidence-Based Nursing (John Wiley & Sons, Inc.), 2025)
Background: Nurse leaders at every level are needed to help organizations achieve strategic goals and deliver safe patient care. Nurse leaders can find fulfillment in their roles; however, they are often prone to poor work‐life balance due to the complexity and demands of their jobs. Professional well‐being, consisting of an individual's overall health and the perception of good work‐related quality of life, is at risk for being compromised in these nurses. Research exploring variables associated with psychosocial well‐being in nurse leaders is limited. Aims: To describe variables related to psychological well‐being in nurse leaders, explore associations among these variables, and identify potential demographic and psychosocial predictors of resilience and burnout. Methods: Participants were a convenience sample of nurse leaders from two hospitals located in the southwestern United States. We used a prospective observational design to describe the incidence of and relationships between self‐compassion, satisfaction with life, resilience, perceived stress, and burnout. We then sought to identify predictors of disengagement and exhaustion (subscales of burnout) and resilience. Results: Participants (n = 105) were mostly female (82.7%) and white (57.7%), while one‐third were charge nurses. Most reported normal to high levels of satisfaction with life (86%), self‐compassion (90%), and resilience (93.3%) and 72.4% reported high stress levels. Moderately high levels of disengagement (46.4%) and exhaustion (59.1%) were also present. Higher self‐compassion levels predicted higher levels of resilience. Lower satisfaction with life and self‐compassion together predicted high disengagement scores, while lower self‐compassion scores predicted high exhaustion scores. Linking Evidence to Action: When disengagement, exhaustion, and perceived stress are elevated, nurse leaders are at risk for low professional well‐being and may be more prone to resignation ideation or turnover. Evidence‐based interventions designed specifically for nurse leaders promoting professional well‐being and emphasizing self‐compassion skills are needed along with high‐quality research on program outcomes.